(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Syllabic discrimination has been adopted as one of the procedures in studies of recombinative reading teaching and acquisition. The objective of this study was to verify the effects of an auditory and visual conditional discrimination training on the acquisition of recombinative reading by three children with cerebral palsy, aged between eight and twelve years. From teaching three words, both of them having two syllables, teaching steps of auditory, visual, auditory-visual and visual-auditory syllables discriminations and rime, onsets, syllabic subtraction and syllabic addition teaching were conducted. One participant read five new words with understanding and the other two participants read four. Data suggest that training caused the formation of partial equivalence classes demonstrated by individuals with decreased communication. Subsequent studies should search for more efficient teaching that use additional procedures to avoid strict control, reexposure to reading tests of recombined words and tests of maintenance performance.